The Role of Service Quality and Location in Increasing Customer Loyalty with Customer Satisfaction as an Intervening Variable - Shoalihin, Shoalihin; Suhaety, Yeye; Lestari, Atun (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
This research aims to determine the effect of service quality and location on customer loyalty with customer satisfaction as an intervening variable for customers of the